The Effect of TiO2 Coating on Pile Penetration Depth in Clay - Nadya Amalia; Asifa Asri; Mamat Rokhmat; S. Sutisna; Sparisoma Viridi; Mikrajuddin Abdullah (Journal of Engineering and Technological Sciences, 2017)
Pile driving tests were conducted using models of concrete piles with titanium dioxide (TiO2) coating and piles without coating. Pile surfaces coated with TiO2 become superhydrophilic, which enables water molecules in clay pores to be attracted to the pile during the pile driving process. The attraction suppresses the compression of the pore water in the clay soil, hence the result of the pile driving tests showed that piles with TiO2 coating could penetrate deeper than piles without coating with the same count of hammer strokes. An examination using FTIR confirmed the formation of bonds between water molecules for piles with coating and the absence of such bonding for piles without coating. Furthermore, it was successfully established that pile surface coating gives different results for pile driving in different clay soils.